ASSESSMENT OF PRESBYOPIA AMONG MOBILE PHONE AND COMPUTER USERS AT PUNJAB, PAKISTAN - Doggar, Shamaila; Jafri, Syeda Rizwana; Anwaar, Rubina; Toor, Rabia Sajjad; Shahbaz, Samia; Rehman, Amna (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find any association between presbyopia and usage of smart phones in Pakistani Population.Study Design: Prospective cross-sectional study.Place and Duration of Study: University of Health Sciences, Lahore, from Oct 2018 to Jul 2019.Methodology: Approval for this prospective cross-sectional study was obtained before hand from the Institutional Review Committee, University of Health Sciences Lahore. Questionnaire was made through Google docs. Data were assessed by using SPSS version-26. Frequency distributions of different demographic characteristics and those of patients’ history with the use of devices were calculated.Results: Median ± Interquartile of age was 36.50 ± 14 as it was not normally distributed variable. Mostly were males (78.9%). Majority belonged to age group of 41-50 years (44.7%). This study participants were mostly of the education group of masters or higher (>50%). About 35% of the study participants were suffering from presbyopia. Out of 182 participants who were suffering from presbyopia majority were using the glasses for near vision for 1-3 years. When the cross tabulation of using the glasses for near vision was done with the duration of usage of mobile phones and computers then it was seen that the result was found to be statistically significant (p=0.04).Conclusion: The usage of smart phones has significantly raised the prevalence of presbyopia and despite knowing all the ocular side effects of using electronic devices the public is still addicted to it.